Implementing Islamic Constitutionalism: How Islamic Is Indonesia Constitution? - Armia, Muhammad Siddiq (al-'adalah, 2018)
Religious constitutionalism has recently become a global discussion. Such a trend arises as a result of several countries that have a majority of religious adherents declare their constitution based on certain religions. Thailand, for example, provides special norms about Buddhism (Buddhist constitutionalism), the Vatican has special norms about Catholicism (Catholic constitutionalism), India has special norms about Hinduism (Hindu constitutionalism), Saudi Arabia has norms specifically about Islam (Islamic constitutionalism), and so on. This article analyzes whether or not the Islamic principles have been adopted in the Indonesian Constitution. These principles consist of protecting religion, soul, mind, offsprings, and property. The author uses the five principles as a standard in measuring the entire Indonesian Constitution which constitutes to the teachings of Islam (Islamic constitutionalism). The implementation of Islamic constitutionalism can be identified through articles in the constitution. This study concluded that, in general, the Indonesian constitution could be considered to have agreed to Islamic constitutionalism, although in some cases it still needs to be actualized more.